Assessment of the impact of the European CO2 emissions trading scheme on the Portuguese chemical industry - Tomas, R. A. F. (2012)
This paper describes an assessment of the impact of the enforcement of the European carbon dioxide (CO2) emissions trading scheme on the Portuguese chemical industry, based on cost structure, CO2 emissions, electricity consumption and allocated allowances data from a survey to four Portuguese representative units of the chemical industry sector, and considering scenarios that allow the estimation of increases on both direct and indirect production costs. These estimated cost increases were also compared with similar data from other European Industries, found in the references and with conclusions from simulation studies. Thus, it was possible to ascertain the impact of buying extra CO2 emission permits, which could be considered as limited. It was also found that this impact is somewhat lower than the impacts for other industrial sectors.